The Slope Assessment Using Geophysical Approaches With Integrated Analysis Of 2-D Cross Plot Model - Zakaria, Muhammad Taqiuddin (2021)
Inadequate resolution with limitation of the methods vulnerable for misinterpretations as characterisation of landslide required a wide range of data and observations. Validation from different parameters necessary to substantiate the result as to reduce erroneous during interpretations. Integrated cross-plot analysis was introduced as an alternative method to enhance the subsurface interpretations based on the models' criteria. Geophysical methods of 2-D resistivity, seismic refraction, and MASW was utilized to characterize the landslide behaviour with supported data from geotechnical and hydrological parameters. Three types of slope conditions were selected, which are the stable slope (USM Archaeology–USM), the critical slope (Lojing–LJ), and the failure slope (Hulu Yam–HY & Bkt Antarabangsa–BA). USM represent the stable slope condition where cohesive soil were identified at resistivity, ρ=400-1000 Ωm and velocity, Vp=800-1800 m/s; Vs= 250-350 m/s at a depth of 5-10 m. Elastic modulus shows the strength of soil with low moduli (Go<0.1 GPa; E<0.25 GPa; ν = 0.05-0.45) with a depth of <5 m. The elastic modulus increases with the depth as shear strength parameters show high range values (c'=5-29 kPa; ϕ'= 21-28.8°). In critical slope (LJ), the residual soil was identified as unconsolidated/weathered material with resistivity, ρ=200-450 Ωm) and velocity, Vp=400-600 m/s; Vs= 150-200 m/s at depth of <5 m. The low values of the moduli (Go<0.1 GPa; E<0.25 GPa; ν= 0.35-0.45) at a depth of <5 m attributed to soil weathering with reducing shear strength parameters. The failure slope of HY and BA shows a highly weathered zone (ρ<1200 Ωm; Vp<1200 m/s) was identified with a depth of <5 m.